PML-RARA Fusion Transcripts Detectable 8 Months prior to Promyelocytic Blast Crisis in Chronic Myeloid Leukemia - Stephanie Wolanin; Robert K. McCall; Mark J. Pettenati; Michael W. Beaty; Giovanni Insuasti-Beltran; Bayard L. Powell; Stacey S. O’Neill (Case Reports in Hematology)
Promyelocytic blast crisis arising from chronic myeloid leukemia (CML) is rare. We present a 40-year-old male who developed promyelocytic blast crisis 17 months after CML diagnosis, confirmed by the presence of the t(15;17) and t(9;22) translocations in the leukemic cells. Preserved nucleic acids from routine BCR-ABL1 testing provided a unique opportunity to evaluate clonal progression over time. Retrospective analysis demonstrated PML-RARA fusion transcripts were first detectable 8 months prior to blast crisis presentation. A review of 21 cases of promyelocytic blasts crisis published in the literature reveals a male predominance with earlier age at onset as compared to females. Interestingly, TKI therapy during chronic phase did not impact the time interval between diagnosis and promyelocytic blast crisis. Treatment with standard acute promyelocytic leukemia regimens provides more favorable outcomes with complete molecular remission. Although rare, it is important to consider a promyelocytic blast crisis when evaluating for transformation of CML due to its effective treatment with specific therapies.